Observation of Unusual, Highly Conductive Grain Boundaries in High‐Mobility Phase Separated Organic Semiconducting Blend Films Probed by Lateral‐Transport Conductive‐AFM. (24th May 2013) - Hunter, Simon; Anthopoulos, Thomas D.
<x xml:space="preserve">Abstract</x> The effect of grain boundaries in high hole mobility organic blend films of diF‐TES ADT:PTAA is evaluated using conductive‐AFM measurements revealing the presence of unusually conductive grain boundaries. The latter characteristic has not been reported previously for any other organic semiconducting film system and is believed to underpin the excellent and morphology‐independent hole transport characteristics seen in these composite films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>